(untitled) (Research, Society and Development, 2020)
The keratocyst is a rare development cyst with high destructive power and can reach large dimensions and a high rate of recurrence. Most of this injury affects men aged 20 to 40 years, affecting the posterior region of the mandible. It can be asymptomatic when in small dimensions even with slow growth, the diagnosis can often be observed in radiographic control exams that are used in our daily clinical practice. The purpose of this case report was to demonstrate the conservative treatment of Odontogenic Keratocyst (OK) in a six-year-old child. The patient underwent an image exam (panoramic radiography) and a surgical procedure with the result of a pathological anatomy. It is important to inform that the objective was achieved with the surgical, but it is worth mentioning that the discomfort caused by the device and the difficulty of cleaning the patient was present. It is noted that the follow-up of this study was for one year and we believe that the patient should continue to attend preventive consultations, due to the high power of recurrence of this pathology. We conclude that decompression was a method used as a conservative treatment and this treatment option continues to be considered successful and much less invasive among the possibilities presented for this type of pathology.